Anti-MRSA Activities of Enterocins DD28 and DD93 and Evidences on Their Role in the Inhibition of Biofilm Formation - Al Atya, Ahmed K.; Belguesmia, Yanath; Chataigne, Gabrielle; Ravallec, Rozenn; Vachée, Anne; Szunerits, Sabine; Boukherroub, Rabah; Drider, Djamel (Frontiers in Microbiology, 2016)
Methicillin-resistant Staphylococcus aureus (MRSA) has become a worrisome superbug. This work aimed at studying the effects of two class IIb bacteriocins, enterocins DD28 and DD93 as anti-MRSA agents. Thus, these bacteriocins were purified, from the cultures supernatants of Enterococcus faecalis 28 and 93, using a simplified purification procedure consisting in a cation exchange chromatography and a reversed-phase high-performance liquid chromatography. The anti-Staphylococcal activity was shown in vitro by the assessment of the minimal inhibitory concentration (MIC), followed by a checkerboard and time-kill kinetics experiments. The data unveiled a clear synergistic effect of enterocins DD28 and DD93 in combination with erythromycin or kanamycin against the clinical MRSA-S1 strain. Besides, these combinations impeded as well the MRSA-S1 clinical strain to setup biofilms on stainless steel and glace devices.